Identifikasi Jenis Gastropoda Pada Zona Intertidal Pantai Deri Dan Pantai Watotena Kecamatan Ile Boleng Kabupaten Flores Timur - Hawan, Florensia Keneka; Bullu, Novi Ivonne; Ballo, Apriliana (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2020)
Gastropods are the class with the largest number of species, because it is a class of mollusk phylum that is most successfulin adapting to various types of marine and freshwater habitats to the terrestrial environment. The research was carried out on the identification of the types of gastropods in the Deri Beach and Watotena Beach with the aim to determine the type of gastropods in the region. The result of researchon the identification of the types of gastropods in the intertidal zone of Deri Beach and Watotena Beach found 9 types of gastropods, including Cypraea caputserpentis 14 individuals, Cypraea moneta 50 individuals, Nerita albicilla 86 individuals, Nerita polita 52 individuals, Nerita costata 39 individuals, Conus flavidus 24 individuals, Cantharus undosus 10 individuals, Morula granulate 213 individuals dan Drupa morum 25 individuals. The result of the calculation of the density obtained the highest density on these two beaches there is the type of Morula granulate which is equal to 2,36 ind/m2 in Deri Beach with a relative density of 60,6%. Based on the calculation of values on both beaches this is categorized as having low diversity because the H’ < 1. Furthermore, in the calculation of the dominance index, values are found on both beaches close to 0 so it is categorized low. In addition, measurements were also taken environmental parameters which include temperature, salinity, pH, and turbidity which result shows that Deri Beach and Watotena Beach have decent conditions for gastropod life.